The Relevance of Complementary and Integrative Medicine in the COVID-19 Pandemic: A Qualitative Review of the Literature - Seifert, Georg; Jeitler, Michael; Stange, Rainer; Michalsen, Andreas; Cramer, Holger; Brinkhaus, Benno; Esch, Tobias; Kerckhoff, Annette; Paul, Anna; Teut, Michael; Ghadjar, Pirus; Langhorst, Jost; et al. (Frontiers in Medicine, 2020)
Background: During the COVID-19 pandemic people are facing risks of adverse health effects due to the restrictions implemented such as quarantine measures, reduced social contact, and self-isolation. In this qualitative review, we collected data on potential preventive and therapeutic health benefits of Complementary and Integrative Medicine (CIM) that might be useful during the COVID-19 pandemic. We have reviewed the scientific literature to summarize CIM practices that could be beneficial for improving physical and mental health and well-being of the population under the current pandemic circumstances. It must be noted that this review is not SARS-CoV-2 specific and we explicitly do not intend to make any SARS-CoV-2 specific health claims in this article. Methods and Findings: A qualitative, non-systematic literature review was conducted in Medline to identify literature describing preventive and therapeutic CIM approaches for strengthening mental and physical health. For a variety of CIM approaches clinical evidence was identified, indicating beneficial effects. CIM approaches include specific dietary measures and selected micronutrients, physical activity, techniques from Mind-Body Medicine, single botanicals or botanical compounds, and spending time in nature among others. The effects of CIM measures on conditions like obesity and hypertension are of special relevance here, as these conditions are considered as risk factors for a severe course of COVID-19. Moreover, a possibly direct effect of CIM approaches on immune functions and clinical parameters in respiratory tract infections, such as influenza, were identified. The findings of this review could be helpful for clinicians, patients and the general population during the current pandemic when discussing and/or considering CIM options. Conclusions: CIM offers a variety of preventive and therapeutic options for strengthening physical and mental resilience, which could also be useful in the current COVID-19 pandemic. The evidence of CIM approaches with a potential benefit in the COVID-19 pandemic in different areas is worth to be analyzed. While this qualitative review has several obvious limitations, it might serve as useful starting point for further research on this topic.